Analisis Semiotika Saussure Pada Poster Series “Girl From Nowhere” Menggunakan metode Ferdinand De Saussure - Putri Julyan, Alya Zahra; Yuliansyah, Tianis (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2023)
Girl From Nowhere is a Thai series from Netflix under GMM Studios. This series has mystery, horror, and thriller genres. Released in 2018. The first episode aired on August 8, 2018. It tells the story of a girl named Nanno whose origins are unknown. The plot of this series revolves around the role of the main character, namely Nanno, a mysterious girl who transfers to various private schools in Thailand. Her role is to reveal the lies, secrets, and hypocrisy of the whole school. Research objective Knowing that every episode of Girl From Nowhere is a true story. The tragedies in this television series are based on case reports in Thailand. That way, these stories are turned into a victory for the girl who is the victim in these cases. By using the Qualitative Approach method. In the film Girl From Nowhere, if it is associated with the theory of semiotics by Ferdinand D Saussure, the signifier and signified that appear are, as a marker of physical form, namely the film Girl From Nowhere and the sign is that the plot of this series revolves around the role of the main character, namely Nanno, a mysterious girl who transfers to various private schools in Thailand with horror, fantasy and mystery genres. Conclusion The stories offered in the Girl from Nowhere series are not the result of mere imagination. The series is inspired by various tragedies that actually happened in Thailand. However, this series was created as a 'happy ending' version for the victims of these tragedies. The victim who is actually suffering is positioned as the winner, while the perpetrator is made to feel the pain experienced by the victim. Keywords: Semiotics, Ferdinand de Saussure, The Girl From Nowhere, Series